2023
DOI: 10.1177/14413582231166066
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Wine Consumers’ Product Evaluation: Effects of Product Involvement, Ethnocentrism, Product Experience and Antecedents

Abstract: This research provides nuanced insights from a consumer-centric behavioural psychology perspective, by developing a theoretically grounded motivational process model of product evaluation, viewed through a country-of-origin (COO) lens, incorporating the focal constructs of product involvement, product knowledge, consumer ethnocentrism (CET) and antecedents related to wine buying in China. An online survey of 934 consumers across China in a range of 12 tier-1 and tier-2 cities investigates the effects of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
(148 reference statements)
0
2
0
Order By: Relevance
“…These findings show that especially when buying wine, country of origin can be a crucial factor that influences consumer decisions. Bruwer et al (2024) state that for wine purchases, the resulting COO effect is influenced by consumer ethnocentrism. Similar results were achieved in the research in this paper, as the highest degree of ethnocentrism is shown by the segment of patriots who exclusively prefer beverages originating from the Czech Republic, including wine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings show that especially when buying wine, country of origin can be a crucial factor that influences consumer decisions. Bruwer et al (2024) state that for wine purchases, the resulting COO effect is influenced by consumer ethnocentrism. Similar results were achieved in the research in this paper, as the highest degree of ethnocentrism is shown by the segment of patriots who exclusively prefer beverages originating from the Czech Republic, including wine.…”
Section: Discussionmentioning
confidence: 99%
“…Several foreign studies have been carried out to examine the COO role in consumer wine-buying behavior. Bruwer et al (2024) investigated the effects of several independent factors on COO product category assessment when buying wine. They found out that consumer ethnocentrism, product involvement, purchasing experience and travel exposure strongly affect COO product category ratings.…”
Section: The Relationship Between Product Category and The Country Of...mentioning
confidence: 99%